Social, economic, environmental and policy aspects of biofuels - Demirbaş, Ayhan (SILA SCIENCE, 2010)
Bioethanol and biodiesel are two alternative fuels promoted with potential to reduce dependence on fossil fuel imports. Biofuels production costs can vary widely by feedstock, conversion process, scale of production and region. The major economic factor to consider for input costs of biodiesel production is the feedstock, which is about 75-80% of the total operating cost. Other important costs are labor, methanol and catalyst, which must be added to the feedstock. The biofuel policy aims to promote the use in transport of fuels made from biomass, as well as other renewable fuels. Biofuels provide the prospect of new economic opportunities for people in rural areas in oil importer and developing countries. Policy drivers for renewable liquid biofuels have attracted particularly high levels of assistance in some countries given their promise of benefits in several areas of interest to governments, including agricultural production, greenhouse gas emissions, energy security, trade balances, rural development and economic opportunities for developing countries.
Keywords: Biodiesel; Bioethanol; Biofuels; Social issues